Kajian Teknis Kebutuhan Genset sebagai Sumber Energi Cadangan di UNTAG Surabaya - Junico Dwi Yussarianto; Giovanni Dimas Prenata (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
To fulfil the needs of electricity, UNTAG Surabaya Building uses electrical energy derived from PLN. But, the provision of electrical energy from PLN unable to constantly supply electrical energy without interruption. So, to overcome it, it’s obligatory to have an electrical energy back-up system in the form of a Genset so electrical energy for building needs is preserved. The Genset works automatically, so when PLN's electrical energy goes out, the generator will immediately work. Conversely, if PLN's electrical energy back to normal, the generator will stop working. Because the electrical energy back-up system at UNTAG Surabaya has been working for really long, it’s obligatory to evaluate also re-analyze the generator back-up system. The analysis is carried out by performing calculations assisted by the ETAP simulation program. For generator efficiency, it is still quite good, which is only 68.25%., because the generator only supplies loads that are an urgent priority. From the simulation results, the load must be provide by the generator is 273.04kW/341.3kVA and the generator capacity used is 400kW/500kVA. In that case, the performance of the genset is still within the limits of its capabilities.